A kind of varistor ceramic powder and its preparation method and application

By introducing Al and Ba elements into the varistor porcelain powder and using rare earth oxide CeO2 to improve additives, the existing zinc oxide varistor has solved the problems of low voltage and small throughput capacity, and a varistor sheet with high potential gradient and throughput capacity is realized to meet the protection needs of modern electronic products.

CN117003559BActive Publication Date: 2025-03-25GUANGDONG FENGHUA ADVANCED TECHNOLOGY (HOLDING) CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310950192.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-07-31
Publication Date
2025-03-25
Estimated Expiration
2043-07-31

AI Technical Summary

Technical Problem

The existing zinc oxide varistors have shortcomings in terms of low voltage and small through-current capacity, which is difficult to meet the protection needs of modern electronic products for high surge voltage and high surge current.

Method used

By introducing a specific weight part of Al and Ba elements into the varistor porcelain powder and adding rare earth oxide CeO2 to the additive, the component ratio of the varistor porcelain powder is optimized to improve the potential gradient and flow capacity.

Benefits of technology

A varistor plate that has achieved low temperature sintering has a high potential gradient and flow capacity. The maximum flow density can reach more than 4000A/cm2, meeting the protection needs of electronic products for high surge voltage and current.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117003559B_ABST
    Figure CN117003559B_ABST
Patent Text Reader

Abstract

The present invention discloses a varistor ceramic powder and a preparation method and application thereof, belonging to the technical field of resistor materials. The present invention introduces specific weight portions of Al and Ba elements into the varistor ceramic powder, introduces rare earth oxides into the additive, and controls the weight portions of each component in the varistor ceramic powder, so that the prepared varistor sheet can be sintered at low temperature and has high potential gradient and current carrying capacity; the maximum current carrying density of the resistor sheet can reach 4000A / cm 2 The above has good performance stability and can be used to prepare ultra-high energy chip varistor materials to meet the use requirements of electronic products such as high surge voltage and large surge current protection.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of resistor materials, and specifically relates to a varistor ceramic powder and a preparation method and application thereof. Background Art

[0002] With the rapid development of electronic circuit components in surface mount technology (SMT) in the fields of communication modules, program-controlled switches, automotive electronics, etc., requirements for varistors have been put forward, such as smaller size, faster response speed, non-polarity, and low limiting voltage. As an overvoltage protection core component, the performance of chip varistors directly affects the stability and safety of electronic equipment operation, and large current capacity and low limiting voltage are important factors for varistors to achieve miniaturization and high energy.

[0003] Zinc oxide (ZnO) varistors have the characteristics of cheap components, simple process, adjustable potential gradient and high nonlinear coefficient, and have been widely used in power systems, rail transit and electrical facility protection. It is a multi-component semiconductor ceramic material formed by mixing, grinding, molding and sintering with ZnO as the main component and various metal oxides such as bismuth oxide, antimony oxide, manganese oxide, niobium oxide and cobalt oxide as additives; according to the different additives, ZnO chip varistors can be divided into bismuth varistors and praseodymium (or rare earth) varistors. Patent KR20130060127A discloses a method for manufacturing a zinc oxide varistor, wherein the varistor is pre-doped with zinc oxide grains of non-equivalent ions according to a preset potential gradient, and then sintered powder is prepared separately according to the preset potential gradient of a specific zinc oxide varistor. The above-mentioned traditional varistors do not meet the requirements of high surge voltage and large surge current for the protection of today's electronic products due to the limitations of low voltage and small current capacity.

[0004] In view of the above problems of varistors, developing a varistor ceramic powder with both high potential gradient and high current carrying capacity is the current research focus in the field of resistor material technology. Summary of the invention

[0005] The purpose of the present invention is to overcome the deficiencies of the above-mentioned prior art and provide a varistor ceramic powder and a preparation method and application thereof. The varistor sheet prepared by the varistor ceramic powder can achieve low temperature sintering and has excellent potential gradient and current carrying capacity.

[0006] To achieve the above object, the technical solution adopted by the present invention is:

[0007] In a first aspect, the present invention provides a varistor ceramic powder, the varistor ceramic powder comprises the following components in parts by weight: 80.0-97.5 parts of ZnO, 0.01-0.06 parts of aluminum salt, 0.01-0.05 parts of barium salt, and 2.0-20.0 parts of additives; the additives comprise the following components: Bi 2 O 3 , Sb 2 O 3 、Co 3 O 4 , Mn 3 O 4 、SiO 2 、TiO 2 , silver glass powder and rare earth oxides.

[0008] The present invention adopts the above components to prepare varistor porcelain powder by compounding. Adding specific weight portions of Al element and Ba element to the porcelain powder is beneficial to improving the grain boundary barrier and reducing the grain resistance, thereby improving the long-term working stability of the varistor, reducing the residual pressure after the lightning energy impact, and enhancing the protection characteristics of the varistor.

[0009] The inventors also found that in the present invention, the addition amount of aluminum salt and barium salt also has a great influence on the performance of the final varistor porcelain powder; if the addition amount of aluminum element is too low, it is difficult to reduce the grain resistance, which reduces the protection of the residual voltage ratio; if the addition amount of aluminum element is too high, the leakage current of the varistor is significantly increased, and the resistance current level is reduced. At the same time, in the present invention, the appropriate amount of Ba is conducive to improving the stability of the grain boundary. Too high or too low Ba element content will affect the structure, composition and properties of the grain boundary phase, thereby having a negative impact on the interface properties between the grains.

[0010] The inventors also found that by introducing rare earth oxides into the additive, the rare earth oxides can act as growth inhibitors of ZnO, partially pinned at the grain boundaries, reducing the mass transfer capacity of interstitial zinc ions, and improving the grain boundary structure and composition of the varistor sheet, so that the prepared varistor sheet can improve the potential gradient of the varistor while maintaining a higher current capacity and a lower leakage current.

[0011] The inventors also found that the weight of the additive in the ceramic powder has a great influence on the performance of the final varistor sheet. If the additive is less than 2.0 parts, the current level, aging resistance and nonlinear coefficient of the varistor will be reduced; if the amount of additive is too large, it will affect the uniformity of the grain size, resulting in an increase in the leakage current of the varistor and an increase in the voltage change rate.

[0012] As a preferred embodiment of the varistor ceramic powder of the present invention, the varistor ceramic powder includes the following components in parts by weight: 86.0-95.5 parts of ZnO, 0.015-0.03 parts of aluminum salt, 0.016-0.035 parts of barium salt, and 6.0-15.0 parts of additives; the inventors found through a large number of experiments that the varistor ceramic powder under the above preferred conditions has the best final comprehensive performance.

[0013] As a preferred embodiment of the varistor ceramic powder of the present invention, the additive comprises the following components in parts by weight: Bi 2 O 3 30.0-60.0 parts, Sb 2 O 3 6.0-20 parts, Co 3 O 4 12.0-28.0 parts, Mn 3 O 4 1.0-8.0 parts, SiO 2 5.0-23.0 parts, TiO 2 0.1-3.0 parts, rare earth oxide 0.2-4.0 parts, silver glass powder 0.5-2.5 parts.

[0014] As a more preferred embodiment of the varistor ceramic powder of the present invention, the additive comprises the following components in parts by weight: Bi 2 O 3 35.0-55.0 parts, Sb 2 O 3 8.0-15 parts, Co 3 O 4 14.0-25.0 parts, Mn 3 O 4 1.0-5.0 parts, SiO 2 10.0-20.0 parts, TiO 2 0.5-2.0 parts, rare earth oxide 0.5-2.0 parts, silver glass powder 0.8-2 parts.

[0015] The inventors have found that when the content of each component in the additive is within the above range, especially within a further preferred range, the potential gradient and current carrying capacity of the obtained varistor are more excellent.

[0016] As a preferred embodiment of the varistor porcelain powder of the present invention, the particle size of the silver glass powder is ≤1 μm, the silver oxide content of the silver glass powder is ≥20wt%, and the bismuth oxide content is ≥30wt%; too low content of silver oxide and bismuth oxide in the silver glass powder will have an adverse effect on the high current impact resistance test of the varistor.

[0017] As a preferred embodiment of the varistor porcelain powder of the present invention, the aluminum salt is aluminum nitrate nonahydrate (Al(NO 3 ) 3 9H 2 O), the barium salt is barium acetate (Ba(AC) 2 ).

[0018] As a preferred embodiment of the varistor ceramic powder of the present invention, the rare earth oxide is Y 2 O 3 ,La 2 O 3 、Nd 2 O 3 or CeO 2 .

[0019] As a more preferred embodiment of the varistor ceramic powder of the present invention, the rare earth oxide is CeO 2 The inventors found through a large number of experiments that the use of CeO 2 The potential gradient and current carrying capacity of the varistor can be maximized.

[0020] As a preferred embodiment of the varistor ceramic powder of the present invention, the varistor ceramic powder further includes a dispersant and a binder.

[0021] In a second aspect, the present invention provides a method for preparing the additive, the method comprising the following steps:

[0022] S1. Mix the additive and the dispersant and pre-disperse them, grind, filter, and crush the pre-dispersed slurry, and pass it through a 30-mesh sieve to obtain a powder;

[0023] S2, calcining the powder in step S1 at a temperature of 650-950° C. for 0.5-4 h, crushing the powder after calcination, and passing it through a 30-mesh sieve;

[0024] S3, refining the powder obtained in step S2 to obtain an additive.

[0025] As a preferred embodiment of the preparation method of the additive of the present invention, in the step S1, the pre-dispersion rotation speed is 500-3000r / min, and the pre-dispersion time is 10-60min; the dispersed slurry is ground in a horizontal sand mill at a grinding rate of 1000-3000r / min and a grinding time of 1-5h; the ground slurry is filtered through a 120-mesh screen, and the filtered additive is dried and crushed at a temperature of 100-130°C.

[0026] As a more preferred embodiment of the method for preparing the additive of the present invention, in the step S1, the pre-dispersion rotation speed is 800-1500 r / min, the pre-dispersion time is 10-30 min; the grinding rate is 1000-2000 r / min, and the grinding time is 1-3 h.

[0027] As a preferred embodiment of the method for preparing the additive of the present invention, in the step S2, the calcination temperature is 700-900°C.

[0028] The inventors have found through a large number of experiments that by adopting the above method and under specific preparation parameters, the various components in the additive are first fully mixed; then the gaseous decomposition products produced by the component reaction are eliminated through step S2, and the valence state change of the variable-valence oxide is completed, so that an additive with a narrow particle size distribution and a small average particle size can be obtained, making it a stable additive complex, which is beneficial to the subsequent solid-phase reaction, reducing the porosity of the porcelain powder and increasing the density of the porcelain powder; then the product is secondary refined through step S3, and the secondary refinement step is the same as step S1, and the purpose is to make the various components of the additive mixed more fully.

[0029] In a third aspect, the present invention provides a method for preparing the varistor ceramic powder, which comprises the following steps: mixing the varistor ceramic powder with a dispersant and a binder and ball-milling the mixture for 12-48 hours, passing the mixture through a 100-mesh sieve after ball-milling, and spray-drying the mixture to obtain the varistor ceramic powder.

[0030] In a fourth aspect, the present invention provides a varistor sheet, wherein the varistor sheet is made of the varistor ceramic powder as described in the first aspect.

[0031] As a preferred embodiment of the varistor sheet of the present invention, the varistor sheet further comprises a dispersant, a defoaming agent and a binder.

[0032] As a preferred embodiment of the varistor sheet of the present invention, the method for preparing the varistor sheet comprises the following steps:

[0033] C1. Mix all the components and then ball-mill for 12-24 hours, and press to form a resistor chip blank;

[0034] C2, debinding, sintering and heat treating the green body described in step C1;

[0035] C3. Silver coating, silver burning, and insulating paint coating are performed on the blank described in step C2 to obtain a varistor sheet.

[0036] As a preferred embodiment of the varistor sheet of the present invention, in the method for preparing the varistor sheet, the density of the blank in step C1 is 3.2-3.3 g / cm 3; The inventors found through a large number of experiments that if the density of the green body is too small, some of the pores in it will be difficult to completely discharge during the sintering process, resulting in an increase in porosity; if the density of the green body is too large, some of the pores in it will form closed pores, which will also lead to an increase in porosity during the subsequent sintering process.

[0037] The inventors have found through a large number of experiments that in step C2, debinding can remove organic matter remaining in the green body, and sintering and heat treatment are beneficial to stabilizing the grain boundary barrier, thereby improving the stability and current carrying capacity of the varistor of the present invention under continuous voltage.

[0038] As a preferred embodiment of the method for preparing the resistor strip of the present invention, in step C2, the debinding temperature is 400-530°C; the sintering parameters are: temperature 900-1080°C, time 1-7h, heating rate 0.5-4.5°C / min; the heat treatment parameters are: temperature 500-650°C, time 1-5h.

[0039] As a more preferred implementation of the method for preparing the resistor strip of the present invention, in the step C2, the debinding temperature is 420-480°C; the sintering parameters are: temperature 900-1000°C, time 2-4h; the heat treatment parameters are: temperature 520-580°C, time 1-3h.

[0040] The inventors have found through a large number of experiments that the varistor sheet prepared under the above preparation parameters has good performance stability and the maximum current density can reach 4000A / cm 2 The above can achieve low temperature sintering and have high potential gradient and flow capacity.

[0041] Compared with the prior art, the present invention has the following beneficial effects:

[0042] The present invention introduces specific weight portions of Al and Ba elements into the varistor porcelain powder, and introduces rare earth oxide CeO into the additive. 2 , and controlling the weight of each component in the varistor ceramic powder, so that the prepared varistor sheet can be sintered at low temperature and have high potential gradient and current capacity; the maximum current density of the resistor sheet can reach 4000A / cm 2 The above has good performance stability and can be used to prepare ultra-high energy chip varistor materials to meet the use requirements of electronic products such as high surge voltage and large surge current protection. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 The present invention is a flow chart of the preparation of the varistor ceramic powder;

[0044] Figure 2 This is a scanning electron microscope image of the varistor sheet according to an embodiment of the present invention;

[0045] Figure 3 This is a scanning electron microscope image of the varistor sheet according to an embodiment of the present invention. DETAILED DESCRIPTION

[0046] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.

[0047] Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0048] Example 1

[0049] The formula of the varistor ceramic powder of Example 1 of the present invention is shown in Table 1, and the formula of the additive is shown in Table 2;

[0050] The preparation method of the additive described in this embodiment comprises the following steps:

[0051] S1. Mix the additive components, water and dispersant in a stainless steel barrel and pre-disperse them. The pre-dispersing speed is 1000r / min and the pre-dispersing time is 15min. The pre-dispersed slurry is transferred to a horizontal sand mill through a constant flow pump for grinding. The grinding rate is 2000r / min and the grinding time is 2h. Then, the ground slurry is filtered through a 120-mesh screen, and the filtered slurry is dried and crushed at 120°C. The crushed slurry is passed through a 30-mesh screen twice and fully mixed to obtain a powder.

[0052] S2, calcining the powder in step S1 at 850° C. for 1 h, crushing the powder after calcination, and passing it through a 30-mesh sieve;

[0053] S3, the powder obtained in step S2 is subjected to secondary refinement, that is, the powder obtained in step S2, water, and dispersant are mixed and pre-dispersed in a stainless steel barrel, the pre-dispersion speed is 1000r / min, and the pre-dispersion time is 15min; the pre-dispersed slurry is transferred to a horizontal sand mill through a constant flow pump for grinding, the grinding rate is 2000r / min, and the grinding time is 2h; then the ground slurry is filtered through a 120-mesh screen, the filtered slurry is dried and crushed at a temperature of 120°C, and the crushed slurry is passed through a 30-mesh screen twice to be fully mixed to obtain an additive.

[0054] The preparation method of the varistor ceramic powder described in this embodiment includes the following steps: mixing the components with water, a dispersant, and a binder in a ball mill and ball milling for 24 hours, passing through a 100-mesh sieve after ball milling, and spray drying using a spray granulator to obtain the varistor ceramic powder.

[0055] The method for preparing the varistor sheet described in this embodiment comprises the following steps:

[0056] C1. The above-mentioned ceramic powder, water, dispersant, binder and defoamer are mixed and ball-milled in a ball mill for 12 hours. After standing for 12 hours, a tablet press is used to press and form a resistor chip body. The side length of the body is 26.8 mm, the thickness is 6.4 mm, and the density is 3.25 g / cm 3 ;

[0057] C2, debinding the green body in step C1 at 500° C., sintering at 950° C. for 5 h, and then heat treating it at 560° C. for 1 h;

[0058] C3. Silver-coat, silver-sinter, and brush-coat the blank described in step C2 with insulating paint to obtain a varistor. The side length of the resistor described in this embodiment is 22.5 mm and the thickness is 5.3 mm.

[0059] Example 2

[0060] The formula of the varistor ceramic powder described in this embodiment is shown in Table 1, and the formula of the additive is shown in Table 2.

[0061] The preparation method of the additive described in this embodiment is different from that in Example 1 only in that: in step S1, the grinding time is 2.5 hours; in step S2, the calcination temperature is 780° C.; the rest is consistent with Example 1.

[0062] The preparation method of the varistor ceramic powder described in this embodiment is the same as that in Example 1.

[0063] The preparation method of the varistor sheet described in this embodiment is different from that of Example 1 only in that: in the step C1, after being placed for 24 hours, a tablet press is used to press and form a resistor sheet blank, and the side length of the blank is 24.6 mm and the thickness is 6.1 mm; in the step C2, it is sintered at 960° C. for 5 hours and then heat-treated at 570° C. for 1 hour; the rest is consistent with Example 1, and the side length of the resistor sheet in this embodiment is 22.5 mm and the thickness is 5.3 mm.

[0064] Example 3

[0065] The formula of the varistor ceramic powder described in this embodiment is shown in Table 1, and the formula of the additive is shown in Table 2.

[0066] The preparation method of the additive described in this embodiment is different from that in Example 1 only in that: in the step S1, the grinding time is 3 hours; in the step S2, the calcination temperature is 750° C.; the rest is consistent with Example 1.

[0067] The preparation method of the varistor ceramic powder described in this embodiment is the same as that in Example 1.

[0068] The preparation method of the varistor sheet described in this embodiment is different from that of Example 1 only in that: in the step C1, after being placed for 24 hours, a tablet press is used to press and form a resistor sheet blank, and the side length of the blank is 28.6 mm and the thickness is 6.5 mm; in the step C2, it is sintered at 960° C. for 7 hours and then heat-treated at 570° C. for 1 hour; the rest is consistent with Example 1, and the side length of the resistor sheet in this embodiment is 24.2 mm and the thickness is 5.5 mm.

[0069] Example 4

[0070] The formula of the varistor ceramic powder described in this embodiment is shown in Table 1, and the formula of the additive is shown in Table 2.

[0071] The preparation method of the additive described in this embodiment is different from that in Example 1 only in that: in step S1, the pre-dispersion time is 25 minutes and the grinding time is 4 hours; in step S2, the calcination temperature is 750° C.; the rest is consistent with Example 1.

[0072] The preparation method of the varistor ceramic powder described in this embodiment is the same as that in Example 1.

[0073] The preparation method of the varistor sheet in this embodiment is different from that in embodiment 1 only in that: in step C1, after being placed for 24 hours, a tablet press is used to press and form a resistor sheet blank, and the side length of the blank is 26.8 mm and the thickness is 6.7 mm; in step C2, it is sintered at 980° C. for 6 hours and then heat treated at 570° C. for 1 hour; the rest is consistent with embodiment 1, the side length of the resistor sheet in this embodiment is 22.5 mm and the thickness is 5.6 mm, and the scanning electron microscope of the varistor sheet is as follows: Figure 2 shown.

[0074] Embodiment 5-8

[0075] The difference between Examples 5-8 of the present invention and Example 1 is that the formula of the varistor ceramic powder is different, as shown in Table 1.

[0076] Examples 9-12

[0077] The difference between Examples 9-12 of the present invention and Example 1 is that the formula of the additives is different, as shown in Table 2.

[0078] Embodiment 13

[0079] The difference between the varistor ceramic powder additive described in Example 13 of the present invention and that described in Example 1 is only that: in the step S2, the calcination temperature is 650° C.; the rest is consistent with Example 1.

[0080] Embodiment 14

[0081] The difference between the varistor ceramic powder additive described in Example 14 of the present invention and that described in Example 1 is only that: in the step S2, the calcination temperature is 950° C.; the rest is consistent with Example 1.

[0082] Comparative Example 1

[0083] The difference between this comparative example and Example 1 is that: the Al(NO 3 ) 3 9H 2 The weight portion of O is 0.005 parts, and the rest is consistent with Example 1.

[0084] Comparative Example 2

[0085] The difference between this comparative example and Example 1 is that: the Al(NO 3 ) 3 9H 2 The weight portion of O is 0.07 parts, and the rest is consistent with Example 1.

[0086] Comparative Example 3

[0087] The difference between this comparative example and Example 1 is that: the Ba(AC) 2 The weight portion is 0.008, and the rest is consistent with Example 1.

[0088] Comparative Example 4

[0089] The difference between this comparative example and Example 1 is that: the Ba(AC) 2 The weight portion is 0.060 parts, and the rest is consistent with Example 1.

[0090] Comparative Example 5

[0091] The difference between this comparative example and Example 1 is that the weight portion of the additive is 1.3 parts, and the rest is consistent with Example 1.

[0092] Comparative Example 6

[0093] The difference between this comparative example and Example 1 is that the weight portion of the additive is 25.6 parts, and the rest is consistent with Example 1.

[0094] Comparative Example 7

[0095] The difference between this comparative example and Example 1 is that CeO is not added to the additive. 2 , the rest are consistent with Example 1.

[0096] Comparative Example 8

[0097] The formula of the varistor ceramic powder and the formula of the additive in this comparative example are the same as those in Example 4.

[0098] The preparation method of the additive described in this embodiment comprises the following steps: grinding the components of the additive, water, a dispersant, and agate balls in a ball mill at a grinding rate of 4500 r / min for 24 h; then filtering the ground slurry with a 120-mesh sieve, drying and crushing the filtered slurry at 120° C., and passing the crushed slurry through a 30-mesh sieve twice to fully mix and obtain the additive.

[0099] The preparation method of the varistor ceramic powder described in this embodiment is the same as that in Example 1.

[0100] The method for preparing the varistor sheet described in this embodiment comprises the following steps:

[0101] C1. The above-mentioned porcelain powder, water, dispersant, binder and defoamer are mixed and ball-milled in a ball mill for 24 hours. After standing for 24 hours, a tablet press is used to press and form a resistor chip body. The side length of the body is 26.8 mm, the thickness is 6.7 mm, and the density is 3.25 g / cm 3 ;

[0102] C2, debinding the green body in step C1 at 500° C., sintering at 980° C. for 6 h, and then heat treating it at 570° C. for 1 h;

[0103] C3, coating the blank in step C2 with silver, burning silver, and brushing with insulating paint to obtain a varistor, wherein the side length of the varistor is 22.5 mm, the thickness is 5.3 mm, and the scanning electron microscope of the varistor is as follows: Figure 3 shown.

[0104] Table 1

[0105]

[0106]

[0107] Table 2

[0108] Weight <![CDATA[Bi 2 THE 3 ]]> <![CDATA[Sb 2 THE 3 ]]> <![CDATA[Co 3 THE 4 ]]> <![CDATA[Mn 3 THE 4 ]]> <![CDATA[SiO 2 ]]> <![CDATA[TiO 2 ]]> <![CDATA[CeO 2 ]]> Silver glass powder Example 1 49.2 12.5 19.3 3.5 10.8 1.7 1.7 1.3 Example 2 47 11.9 18.5 3.3 14.9 1.6 1.6 1.2 Example 3 48.3 11.9 18.5 3.2 13.9 1.5 1.5 1.2 Example 4 52.2 10.3 17.9 2.7 12.5 1.4 1.4 1.2 Example 5 49.2 12.5 19.3 3.5 10.8 1.7 1.7 1.3 Example 6 49.2 12.5 19.3 3.5 10.8 1.7 1.7 1.3 Example 7 49.2 12.5 19.3 3.5 10.8 1.7 1.7 1.3 Example 8 49.2 12.5 19.3 3.5 10.8 1.7 1.7 1.3 Example 9 35.0 15.0 14.0 1.0 10.0 2.0 0.5 2.0 Example 10 55.0 8.0 25.0 5.0 20.0 0.5 2.0 0.8 Embodiment 11 30.0 6.0 28.0 1.0 23.0 0.1 4.0 0.5 Example 12 60.0 20 12.0 8.0 5.0 3.0 0.2 2.5

[0109] Performance Testing

[0110] The electrical properties of the varistor sheets prepared in the above examples and comparative examples were tested, and the results are shown in Table 3 below.

[0111] Table 3

[0112]

[0113]

[0114]

[0115] The finished product size of the varistor sheet prepared by the present invention is 10-30 mm in side length and 2-15 mm in thickness. The results in Table 3 show that the potential gradient range of the varistor sheets of Examples 1-14 can reach 300-550 V / mm, the nonlinear coefficient is 30-80, and the peak current density can reach 3000-4500 A / cm in the 8 / 20 μs lightning wave impulse test. 2 , especially the peak current density of Examples 1-6 and 9-10 is higher.

[0116] In Comparative Examples 1-4, since the weight proportion of aluminum salt or barium salt is not within the scope of the present invention, the peak current density of the finally prepared varistor in the 8 / 20μs lightning wave impact test is low; in Comparative Examples 5 and 6, since the weight proportion of the additive is not within the scope of the present invention, the various properties of the final varistor are not as good as those of the embodiments; in Comparative Example 7, no rare earth oxide is added to the additive, and the potential gradient of the final resistor is lower, and the peak current density is lower.

[0117] By comparing Example 4 and Comparative Example 8 separately, it is found that when preparing the additive in Comparative Example 8, the traditional ball milling method is adopted, and the additive is not subjected to calcination and secondary refinement process. Table 3 shows that the peak current density of the resistor described in Comparative Example 8 in the 8 / 20μs lightning wave impact test is only 1950A / cm 2 ;and Figure 2 , 3 Relatively restrained, the additive preparation process of the present invention adopts a horizontal grinder instead of the traditional ball milling method, which can not only improve the grinding efficiency of the additive, but also significantly improve the microstructural uniformity of the varistor; the method of the present invention can reduce the porosity of the porcelain body and increase the density of the ceramic, thereby enhancing the electrical capacity of the varistor.

[0118] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A varistor ceramic powder, characterized in that: The varistor porcelain powder comprises the following components in parts by weight: 86.0-95.5 parts of ZnO, 0.015-0.03 parts of aluminum salt, 0.016-0.035 parts of Ba(AC)2, and 6.0-15.0 parts of additives; The preparation method of the additive comprises the following steps: S1, the additive is mixed with the dispersant, and pre-dispersed, the pre-dispersed slurry is ground, filtered, crushed, and passed through a 30-mesh sieve to obtain a powder; The additive comprises the following components in parts by weight: 30.0-60.0 parts of Bi2O3, 6.0-20 parts of Sb2O3, 12.0-28.0 parts of Co3O4, 1.0-8.0 parts of Mn3O4, 5.0-23.0 parts of SiO2, 0.1-3.0 parts of TiO2, 0.2-4.0 parts of rare earth oxide, and 0.5-2.5 parts of silver glass powder; S2, calcining the powder in step S1 at a temperature of 650-950° C. for 0.5-4 h, crushing the powder after calcination, and passing it through a 30-mesh sieve; S3, refining the powder obtained in step S2 to obtain an additive; In step S1, the grinding is performed using a horizontal grinding machine; The rare earth oxide is CeO2.

2. The varistor ceramic powder according to claim 1, characterized in that: The additive includes the following components in parts by weight: 35.0-55.0 parts of Bi2O3, 8.0-15 parts of Sb2O3, 14.0-25.0 parts of Co3O4, 1.0-5.0 parts of Mn3O4, 10.0-20.0 parts of SiO2, 0.5-2.0 parts of TiO2, 0.5-2.0 parts of rare earth oxide, and 0.8-2 parts of silver glass powder.

3. The varistor ceramic powder according to claim 1, characterized in that: In the preparation method of the additive, in step S1, the pre-dispersion parameters are: rotation speed of 500-3000 r / min, time of 10-60 min; the grinding parameters are: rate of 1000-3000 r / min, time of 1-5 h.

4. The method for preparing the varistor ceramic powder according to any one of claims 1 to 3, characterized in that: The method comprises the following steps: mixing the varistor ceramic powder according to any one of claims 1 to 3 with a dispersant and a binder, and ball milling the mixture for 12 to 48 hours; passing the mixture through a 100-mesh sieve after ball milling; and drying the mixture to obtain the varistor ceramic powder.

5. A varistor sheet, characterized in that: The varistor sheet is made of the varistor ceramic powder according to any one of claims 1 to 3.

6. The varistor sheet according to claim 5, characterized in that: The method for preparing the varistor sheet comprises the following steps: C1. Mix the ceramic powder according to any one of claims 1 to 3 with a dispersant, a binder and a defoamer, and then ball-mill for 12 to 24 hours, and press to form a resistor chip body; C2, debinding, sintering and heat treating the green body described in step C1; C3, coating the blank described in step C2 with silver, burning silver, and brushing with insulating paint to obtain the varistor sheet.

Citation Information

Patent Citations

  • Process for producing zinc oxide varistor having high potential gradient and high non-linearity coefficient

    KR1020130060127A

  • Preparation method of zinc oxide piezoresistor with rare earth oxide additive subjected to solution treatment in advance

    CN112341186A